For your eyes only: effect of confederate’s eye level on reach-to-grasp action - Quesque, François (Front Psychol, 2014)
Previous studies have shown that the spatio-temporal parameters of reach-to-grasp movement are influenced by the social context in which the motor action is performed. In particular, when interacting with a confederate, movements are slower, with longer initiation times and more ample trajectories, which has been interpreted as implicit communicative information emerging through voluntary movement to catch the partner’s attention and optimize cooperation (Quesque et al., 2013). Because gaze is a crucial component of social interactions, the present study evaluated the role of a confederate’s eye level on the social modulation of trajectory curvature. An actor and a partner facing each other took part in a cooperative task consisting, for one of them, of grasping and moving a wooden dowel under time constraints. Before this Main action, the actor performed a Preparatory action, which consisted of placing the wooden dowel on a central marking. The partner’s eye level was unnoticeably varied using an adjustable seat that matched or was higher than the actor’s seat. Our data confirmed the previous effects of social intention on motor responses. Furthermore, we observed an effect of the partner’s eye level on the Preparatory action, leading the actors to exaggerate unconsciously the trajectory curvature in relation to their partner’s eye level. No interaction was found between the actor’s social intention and their partner’s eye level. These results suggest that other bodies are implicitly taken into account when a reach-to-grasp movement is produced in a social context.